Synergistic Integration of Mesocarbon Microbeads, Graphitic Nanofibers, and Mesoporous Carbon for Advanced Supercapacitor Electrodes - Palanisamy Rajkumar; Vediyappan Thirumal; Kisoo Yoo; Jinho Kim (Crystals)
In this study, a novel multiscale carbon architecture was developed by integrating mesocarbon microbeads (MCMBs), graphitic nanofibers (GNFs), and mesoporous carbon, aimed at enhancing the performance of symmetric supercapacitors. The unique combination of spherical MCMB particles, conductive GNF nanofibers, and mesoporous carbon sheets resulted in a highly effective electrode material, offering improved conductivity, increased active sites for charge storage, and enhanced structural stability. The fabricated MCMB/GNF/MC architecture demonstrated a remarkable specific capacitance of 393 F g−1 at 1 A g−1 in a three-electrode system, significantly surpassing the performance of individual MCMBs and MCMB/GNF electrodes. Furthermore, the architecture was incorporated into a symmetric supercapacitor (SSC) device, where it achieved a capacitance of 86 F g−1 at 1 A g−1. The device exhibited excellent cycling stability, retaining 92% of its initial capacitance after 10,000 charge–discharge cycles, with an outstanding coulombic efficiency of 99%. At optimal operating conditions, the SSC device delivered an energy density of 11 Wh kg−1 at a power density of 500 W kg−1, making it a promising candidate for high-performance energy-storage applications. This multiscale carbon architecture represents a significant advancement in the design of electrode materials for symmetric supercapacitors, offering a balance of high energy and power density, long-term stability, and excellent scalability for practical applications. This work not only contributes to the development of high-performance electrode materials but also paves the way for scalable, long-lasting supercapacitors for future energy-storage technologies.